Investigating Cooperative Purchasing Performance - A Survey Of Purchasing Professionals In Dutch Hospitals - Cees Johannes Gelderman; Jelle De Jonge; Jos Schijns; Janjaap Semeijn (The Central European Review of Economics and Management (CEREM), 2018)
Aim: Cooperative purchasing is considered a promising area for lowering the cost in the health care sector, although recent initiatives show mixed results. The purpose of this study is to find a thorough explanation for the performance of cooperative purchasing in healthcare by investigating the role of trust, commitment, organizational factors (i.e. group formality, and IT system effectiveness) and interpersonal skills (i.e. teamwork skills, and communication).Design/research method: A conceptual model for the performance of cooperative purchasing was developed. This model was empirically validated using a survey of 88 Dutch hospital purchasing professionals.Conclusions/findings: Analysis shows a significant impact of trust and commitment in cooperative purchasing groups on performance. Group formality and teamwork skills appear to be essential for achieving trust and cooperative purchasing performance. We also found a positive impact of IT system effectiveness on commitment, not on trust. Positive feelings about the group and positive expectation about the continuity of the group can be stimulated through effective IT systems. Since proper IT support is often neglected in many healthcare organizations, management efforts to improve IT systems could truly facilitate the tactical purchasing process of cooperative purchasing in hospitals.Originality/value of the article: Many cooperative purchasing initiatives suffer from conflicts over the allocation of savings, time, and costs. Despite the growing importance of cooperative purchasing, few empirical studies have explored the effects on hospital performance. Our study extends previous research by investigating the relationships between trust, commitment, and the performance of cooperative purchasing (1) and the impact of organizational factors and interpersonal skills on trust and commitment in purchasing groups within a healthcare context (2).
Keywords: M1; 330; cooperative purchasing; healthcare; trust; commitment; cooperative purchasing performance